METHODOLOGY FOR FORMING A SYNTHESIS OF SINGING MANNERS IN MODERN PERFORMANCE - Viktorova, Margarita; Kosyak, Lyudmyla (SWorldJournal, 2025)
The work examines the issues of the formation of the synthesis of singing manners in modern performance; the concepts of "singing manner", "universal singer" are characterized; the scientific works of leading specialists on the main issue are analyzed; t